First-in-man six-month results of a surface-modified coronary stent system in native coronary stenosis - Pannipa Suwannasom (2018)
© Europa Digital & Publishing 2017. All rights reserved. Aims: In preclinical studies, a bare metal cobalt-chromium stent with an active surface oxide layer modification (BMSmod) has been shown to inhibit neointimal hyperplasia effectively. We sought to assess both the clinical safety and feasibility of the BMSmod. Methods and results: In this prospective, non-randomised, first-in-man multicentre study, a total of 31 patients with de novo coronary lesions, reference lumen diameters of 2.5-3.5 mm and lesion length ≤16 mm, were enrolled. Quantitative coronary angiography and optical coherence tomography (OCT) were performed at baseline and six-month follow-up. Primary angiographic and OCT endpoints included in-stent late lumen loss (LLL) and mean neointimal thickness at six months. The device-oriented composite end-point (DoCE), defined as cardiac death, myocardial infarction not clearly attributable to a non-intervention vessel, and clinically indicated target lesion revascularisation (CI-TLR), was analysed according to the intention-to-treat princi ple. In 31 patients (33 lesions), the procedural success rate was 93.5%. At six months, angiographic LLL was 0.91±0.45 mm and binary angiographic restenosis occurred in 23.3% of lesions. Out of 33 lesions, OCT was performed in 27 lesions at both time points. Mean neointimal thickness amounted to 348±116 μm. At six months, the DoCE was 19.4% due to the occurrence of CI-TLR in five patients (including one late definite stent thrombosis of a non-study stent). Conclusions: In contrast to previous preclinical pathophysiological work, the BMSmod did not prevent neointimal hyperplasia in a first-in-man clinical setting.